Śrīmadbhagavatīsūtram (pañcadaśaṃ gośālakākhyaṃ śatakam) - Vaidya, N. V. 1907-; Abhayadevasūri -1082 (Bombay The Managing Trustess of the Godiji Jain Temple and Charities, 1954)
Jaina canonical text, with Sanskrit commentary by Abhayadevasūri, 11th cent
Includes index
Text in Devanāgarī-Schrift Sanskrit und Prakrit, Einleitung Englisch
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jaina Āgama -- Commentaries; Jaina Āgama; Commentaries; Quelle; Kommentar